Evaluation of Relationship Between Testicular Dose and Hormonal Changes After Radiotherapy in Patients With Rectal Cancer - Sourati, Ainaz; Malekzadeh, Mona; Bakhshandeh, Mohsen; Moosavizadeh, Ahmad; Azma, Zohre (Reports of Radiotherapy and Oncology, 2015)
Background: Colorectal cancer globally affects more than 1 million people every year. It is more common in men and it is the second most common cause of cancer mortality. Optimal treatment of colorectal cancer is a multidisciplinary approach which can be included of surgery, medical oncology, and radiation therapy. Objectives: The aim of this study was evaluation of relationship between testicular dose and hormonal changes after radiotherapy in male patients with rectal cancer. Patients and Methods: In this study 25 patients with rectal cancer were enrolled. The serum levels of luteinize hormone (LH), follicle stimulating hormone (FSH), and testosterone (T) before and 3 - 6 weeks after chemoradiotherapy were compared and testicular dose was determined using a 3-dimension treatment planning system and relationship between hormonal changes and testicular dose was assessed. Results: 25 patients with rectal cancer with mean (± SD) age of 56.08 (± 14.30) years were evaluated. The mean (± SD) testes dose was 2.35 (± 2.32) Gy that was 6.09% of total dose. The levels of FSH and LH significantly increased (P = 0.001), however, the level of testosterone non -significantly decreased after 3 - 6 weeks of radiation therapy (P = 0.79). No significant correlation was found between testes dose and sex hormones change (LH, P = 0.33; FSH, P = 0.16; testosterone, P = 0.95). Furthermore the testes dose did not correlate with the lower border of treatment field (P = 0.26), total given dose to the patients (P = 0.81) and tumor location (P = 0.09). Conclusions: The testes dose in this study was 6.09% of total dose. Radiotherapy of rectal cancer causes damage to the testis, as shown by increased levels of gonadotropins after radiotherapy. The radiation therapy significantly increased LH, FSH and non-significantly decreased testosterone level in patients with rectal cancer. No correlation could be found between changes of hormones and doses to the testis, probably due to the low number of evaluated patients. Larger studies are needed to establish the correlation between testicular radiation dose and hormonal changes in this group of patients.